2014
DOI: 10.1089/ars.2013.5777
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling Alterations, Oxidative Stress, and Autophagy in Aging

Abstract: A better understanding of Ca(2+) signaling and molecular aging alterations is important for preventing apoptosis in age-related diseases. In addition, caloric restriction, resveratrol and autophagy modulation appear to be predominantly cytoprotective, and further studies of this process are promising in age-related disease therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
89
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 199 publications
(173 reference statements)
0
89
0
1
Order By: Relevance
“…In particular, excessively high glutamate levels in synaptic terminals leads to calcium overload, which contributes to death during brain aging and in many neurodegenerative conditions. 28 In the rd1 model of retinitis pigmentosa, abnormal calcium accumulation in photoreceptor cells has been linked to cell death independently of cGMP levels. 29 Several studies have also implicated intracellular calcium in autophagy regulation, 30 and the differing outcomes described suggest that calciumdependent autophagy regulation may be both cell-and context-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, excessively high glutamate levels in synaptic terminals leads to calcium overload, which contributes to death during brain aging and in many neurodegenerative conditions. 28 In the rd1 model of retinitis pigmentosa, abnormal calcium accumulation in photoreceptor cells has been linked to cell death independently of cGMP levels. 29 Several studies have also implicated intracellular calcium in autophagy regulation, 30 and the differing outcomes described suggest that calciumdependent autophagy regulation may be both cell-and context-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that intracellular Ca 2C signaling is involved in autophagy. 100,101 Although it has been suggested that autophagy may be activated by an increase in cytosolic Ca 2C concentration or a perturbed release from intra-or extracellular stores, 100 more compelling evidence has indicated that an increase in intracellular Ca 2C inhibits autophagic flux. [102][103][104] Both mitochondria and the ER play a critical role in Ca 2C homeostasis and regulation of autophagy.…”
Section: Calcium Signaling Intracellular Camentioning
confidence: 99%
“…In fact, mitochondria are located where high amounts of ATP are required (34) and also where Ca 2 + signaling needs tight regulation (126). Importantly, alterations in mitochondrial Ca 2 + have been related to several pathologies, including neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS) (318), and aging (332). In recent years, it has been demonstrated that mitochondria actively interact with ER membranes through structuredenominated mitochondria-associated membranes, which enable direct and rapid exchange of lipids and Ca 2 + between the two compartments.…”
mentioning
confidence: 99%